Factors associated with COVID-19 vaccine uptake in people with kidney disease: an OpenSAFELY cohort study. Issue 1 (31st January 2023) - ,; Parker, Edward PK; Tazare, John; Hulme, William J; Bates, Christopher; Carr, Edward J; Cockburn, Jonathan; Curtis, Helen J; Fisher, Louis; Green, Amelia CA; Harper, Sam; Hester, Frank; et al.
Abstract : Objective: To characterise factors associated with COVID-19 vaccine uptake among people with kidney disease in England. Design: Retrospective cohort study using the OpenSAFELY-TPP platform, performed with the approval of NHS England. Setting: Individual-level routine clinical data from 24 million people across GPs in England using TPP software. Primary care data were linked directly with COVID-19 vaccine records up to 31 August 2022 and with renal replacement therapy (RRT) status via the UK Renal Registry (UKRR). Participants: A cohort of adults with stage 3–5 chronic kidney disease (CKD) or receiving RRT at the start of the COVID-19 vaccine roll-out was identified based on evidence of reduced estimated glomerular filtration rate (eGFR) or inclusion in the UKRR. Main outcome measures: Dose-specific vaccine coverage over time was determined from 1 December 2020 to 31 August 2022. Individual-level factors associated with receipt of a 3-dose or 4-dose vaccine series were explored via Cox proportional hazards models. Results: 992 205 people with stage 3–5 CKD or receiving RRT were included. Cumulative vaccine coverage as of 31 August 2022 was 97.5%, 97.0% and 93.9% for doses 1, 2 and 3, respectively, and 81.9% for dose 4 among individuals with one or more indications for eligibility. Delayed 3-dose vaccine uptake was associated with younger age, minority ethnicity, social deprivation and severe mental illness—associations that were consistent across CKD severity subgroups, dialysis patients and kidney transplant recipients. Similar associations were observed for 4-dose uptake. Conclusion: Although high primary vaccine and booster dose coverage has been achieved among people with kidney disease in England, key disparities in vaccine uptake remain across clinical and demographic groups and 4-dose coverage is suboptimal. Targeted interventions are needed to identify barriers to vaccine uptake among under-vaccinated subgroups identified in the present study.